Human Papillomavirus - Research in a Global Perspective 2016
DOI: 10.5772/63295
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Human Papillomavirus and Colorectal Carcinogenesis

Abstract: Colorectal, colon and rectal, cancer is the third most common malignancy in both men and women worldwide. Colorectal carcinogenesis is a complex, multistep process implicating environmental and lifestyle factors in addition to gene mutation and viral infections. On the other hand, it is well established that human papillomaviruses (HPVs) infection play a crucial role in certain types of human carcinomas including cervical and head and neck (HN); as roughly 96% and 30% of these cancers are positive for high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…Finally, reveal that in human normal epithelium and tumor cells, the cooperative influence of E6 and E7 through ErbB-2 is induce by -catenin tyrosine phosphorylation and activation of pp60 (c-Src) kinase [30]. Thus, collaboration with both E6&E7 E6&E7 oncoproteins from highrisk HPVs and other oncogenes may aid in the development of colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 95%
“…Finally, reveal that in human normal epithelium and tumor cells, the cooperative influence of E6 and E7 through ErbB-2 is induce by -catenin tyrosine phosphorylation and activation of pp60 (c-Src) kinase [30]. Thus, collaboration with both E6&E7 E6&E7 oncoproteins from highrisk HPVs and other oncogenes may aid in the development of colorectal cancer [31].…”
Section: Discussionmentioning
confidence: 95%
“…Like psoriasis, HPV positivity resulted in an increased risk of colorectal carcinoma, and HPV infection has been suggested to be a co-factor in the pathogenesis of colorectal cancer [ 82 , 83 ]. Small population studies have shown that colorectal infection with high-risk HPV types is common in colorectal cancer patients, but large population studies have failed to replicate this finding [ 84 , 85 , 86 , 87 ]. In any case, the exact role that HPV plays in colorectal tumor carcinogenesis is remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), DM will be the seventh prime cause of death in 2030 [5]. The International Diabetes Federation (IDF) has figured that by 2021, 536.6 million will be living with diabetes, and by 2045, this figure is forecasted to elevate by 46%, reaching 783.2 million [6]. However, the microvascular (stroke, cardiovascular ailment, and peripheral artery disease) and macrovascular (nephropathy, neuropathy, and retinopathy) problems are the two main chronic complications of the disease with the former having more presence than the latter [6].…”
Section: Introductionmentioning
confidence: 99%
“…The International Diabetes Federation (IDF) has figured that by 2021, 536.6 million will be living with diabetes, and by 2045, this figure is forecasted to elevate by 46%, reaching 783.2 million [6]. However, the microvascular (stroke, cardiovascular ailment, and peripheral artery disease) and macrovascular (nephropathy, neuropathy, and retinopathy) problems are the two main chronic complications of the disease with the former having more presence than the latter [6]. Owing to the high prevalence of the disease, the poor health consequences and surge in the costs of treatment make it obligatory to focus on early diagnosis with the consequent alterations in the management of DM [6].…”
Section: Introductionmentioning
confidence: 99%